Transmission Dynamics of Hyper-Endemic Multi-Drug Resistant Klebsiella pneumoniae in a Southeast Asian Neonatal Unit: A Longitudinal Study With Whole Genome Sequencing - Smit, Pieter W.; Stoesser, Nicole; Pol, Sreymom; van Kleef, Esther; Oonsivilai, Mathupanee; Tan, Pisey; Neou, Leakhena; Turner, Claudia; Turner, Paul; Cooper, Ben S. (Frontiers in Microbiology, 2018)
Background: Klebsiella pneumoniae is an important and increasing cause of life-threatening disease in hospitalised neonates. Third generation cephalosporin resistance (3GC-R) is frequently a marker of multi-drug resistance, and can complicate management of infections. 3GC-R K. pneumoniae is hyper-endemic in many developing country settings, but its epidemiology is poorly understood and prospective studies of endemic transmission are lacking. We aimed to determine the transmission dynamics of 3GC-R K. pneumoniae in a newly opened neonatal unit (NU) in Cambodia and to address the following questions: what is the diversity of 3GC-R K. pneumoniae both within- and between-host; to what extent is high carriage prevalence driven by ward-based transmission; and to what extent can environmental contamination explain patterns of patient acquisition. Methods: We performed a prospective longitudinal study between September and November 2013. Rectal swabs from consented patients were collected upon NU admission and every three days thereafter. Morphologically different colonies from swabs growing cefpodoxime-resistant K. pneumoniae were selected for whole-genome sequencing (WGS). Results: 158 samples from 37 patients and seven environmental sites were collected. 32/37 (86%) patients screened positive for 3GC-R K. pneumoniae and 93 colonies from 119 swabs were successfully sequenced. Isolates were resistant to a median of six (range 3-9) antimicrobials. WGS revealed high diversity; pairwise distances between isolates from the same patient were either 0-1 SNV or >1,000 SNVs; 19/32 colonized patients harboured K. pneumoniae colonies differing by >1000 SNVs. Diverse lineages accounted for 18 probable importations to the NU and nine probable transmission clusters involving 19/37 (51%) of screened patients. Median cluster size was 5 patients (range 3-9). Seven out of 46 environmental swabs (15%) were positive for 3GC-R K. pneumoniae. Environmental sources were plausible sources for acquisitions in 2/9 transmission clusters, though in both cases other patients were also plausible sources. Conclusions: The epidemiology of 3GC-R K. pneumoniae was characterised by multiple introductions, high within- and between host diversity and a dense network of cross-infection, with half of screened neonates part of a transmission cluster. We found no evidence to suggest that environmental contamination was playing a dominant role in transmission.